2021
DOI: 10.1080/08959420.2021.1927614
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Assets of Older Adults in Sub-Saharan Africa: Perspectives of Gerontology Scholars

Abstract: Life expectancy is increasing globally, with the biggest gains expected in sub-Saharan Africa.Using an online survey we investigated the perspectives of gerontology scholars on the challenges of aging in sub-Saharan Africa as well as the assets of elders. Respondents (n=72) from 17 countries, primarily in Africa, and representing 16 disciplines, identified the top issues facing African elders as: poverty, lack of trained geriatric professionals, food insecurity, disability/health issues, and long-term care. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…In SSA, issues affecting aging are rooted in regrettable and implicit social and contextual conditions. For instance, social warfare for older adults’ care is almost nonexistent in some nations because of several reasons, including but not limited to inadequate government resources and funding, inadequate policy frameworks, and cultural beliefs and attitudes towards older adults ( Aboderin & Beard, 2015 ; Aboderin & Ferreira, 2008 ; Adamek et al, 2021 ; National Research Council, 2006 ; Saka et al, 2019 ). A 2022 study reported that 72 gerontological scholars from 17 countries stated that the lack of social services targeted at older adults could result from competing priorities in addressing other societal needs for other populations ( Adamek et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In SSA, issues affecting aging are rooted in regrettable and implicit social and contextual conditions. For instance, social warfare for older adults’ care is almost nonexistent in some nations because of several reasons, including but not limited to inadequate government resources and funding, inadequate policy frameworks, and cultural beliefs and attitudes towards older adults ( Aboderin & Beard, 2015 ; Aboderin & Ferreira, 2008 ; Adamek et al, 2021 ; National Research Council, 2006 ; Saka et al, 2019 ). A 2022 study reported that 72 gerontological scholars from 17 countries stated that the lack of social services targeted at older adults could result from competing priorities in addressing other societal needs for other populations ( Adamek et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, social warfare for older adults’ care is almost nonexistent in some nations because of several reasons, including but not limited to inadequate government resources and funding, inadequate policy frameworks, and cultural beliefs and attitudes towards older adults ( Aboderin & Beard, 2015 ; Aboderin & Ferreira, 2008 ; Adamek et al, 2021 ; National Research Council, 2006 ; Saka et al, 2019 ). A 2022 study reported that 72 gerontological scholars from 17 countries stated that the lack of social services targeted at older adults could result from competing priorities in addressing other societal needs for other populations ( Adamek et al, 2021 ). Our finding, alongside previous evidence, highlighted the need for aging research in SSA to refocus on social- and contextual-related areas, identifying the economic and social inequalities that may contribute to lack of resources and support for the older adult’s population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have contemplated key issues such as HIV/AIDs-related role reversal, intergenerational dependency, aging in place, access to health care, formal and informal social security systems, retirement homes, poverty, impacts of communicable and non-communicable, etc. [ 12 ]. Similarly, Kalu et al conducted a systematic mapping review involving 512 ageing studies in SSA which showed that most studies focused on non-communicable diseases and HIV/AIDs, Cancer, and physical functioning [see [ 3 ] for full details].…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, while just 5% of the population is age 65 and over, it is expected that the country will have 11.5 million older adults by 2050 (Central Statistical Agency of Ethiopia 2007). Despite sub-Saharan Africa having the biggest gains in life expectancy (United Nations 2019), gerontological studies in the region remain sparse (Adamek et al 2021). In the absence of systematic inquiries in Ethiopia and other Sub-Saharan nations, we have little insight into the lives of scores of undocumented centenarians, including cultural differences in their profile, lifestyles, and needs.…”
Section: Introductionmentioning
confidence: 99%